2021
DOI: 10.21608/epsj.2021.195201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nigella Sativa Seeds on Broiler Chicks Hematological, Blood Biochemical Parameters and Antioxidant Enzymes

Abstract: The present study targets to look deep at the influence of Nigella sativa seeds (NSS) supplementation on hematological, blood biochemical measurements, liver and kidney functions and antioxidant enzymes of Arbor Acres broiler chicks. A total of 140 unsexed one day old Arbor Acres broiler chicks were randomly divided into four treatment groups during the period from 1-35 days of age. The chicks were randomly assigned in a straight run experimental design among four treatments, each replicated 7 times with 5 uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(36 reference statements)
3
3
0
Order By: Relevance
“…Our results agree with those of Abou El-Maaty et al ( 2021 ), who reported significant increases in serum concentrations of the antioxidant enzymes (CAT and SOD) and FSH and T3 hormones in broiler chickens fed diets containing 7.5% RSM compared with their control birds. Consistent with the present results, Hassan ( 2021 ) found that feeding diets containing Nigella sativa seeds to broiler chicks caused a significant increase in blood plasma activity of catalase and glutathione reductase compared with the control group. It is well-known that thyroid hormones are vital regulators of metabolic processes and that T3 is the active form of these hormones.…”
Section: Resultssupporting
confidence: 91%
“…Our results agree with those of Abou El-Maaty et al ( 2021 ), who reported significant increases in serum concentrations of the antioxidant enzymes (CAT and SOD) and FSH and T3 hormones in broiler chickens fed diets containing 7.5% RSM compared with their control birds. Consistent with the present results, Hassan ( 2021 ) found that feeding diets containing Nigella sativa seeds to broiler chicks caused a significant increase in blood plasma activity of catalase and glutathione reductase compared with the control group. It is well-known that thyroid hormones are vital regulators of metabolic processes and that T3 is the active form of these hormones.…”
Section: Resultssupporting
confidence: 91%
“…These results are consistent with the result of the present study that supplementation of 0.5%, 1%, and 2% NS to the diet did not affect slaughter, hot carcass, wing, liver and heart weights, compared to the control group.In some studieswith broilers; Amadand Mohammed(2013) found that the addition of 1.5%, 2.5%, and 3.5% NS did not affect slaughter weight, carcass yield, and edible visceral rates; Kumar et al (2018) stated that slaughter weight, carcass yield, breast, thigh, wing, neck, liver, and abdominal fat weight, and total edible visceral weight increased or tended to increase with the addition of 0.5%, 1% and 2% black cumin Although kidney MDA values showed a tendency to decrease in the NS groups, this decrease was not significant compared to the control group. Similar to this study, Hassan (2021) reported that 0.5%, 1%, and 1.5% black cumin supplementation did not affect the plasmaMDA level in broiler chickens. Likewise, Aydoganet al (2020) reported that 0.5% NS supplementation did not affect serum total antioxidant and oxidant levels.…”
Section: Discussionsupporting
confidence: 89%
“…In studies similar to this study, it has been reported that thymoquinone, the main active ingredient of black cumin, 6000 F. KAZAK, T. CIMRIN, S. ALASAHAN, M.A. KISACAM, T. KUTLU increases CAT and GPx activities (El-Hack et al, 2018;Harzallah et al, 2012;Hassan, 2021;Sogut et al, 2008). It has also been reported to have lipid peroxidation inhibitory effects and antioxidant activity (Harzallah et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations